Editor’s Introduction: - Crag Hill (Study and Scrutiny, 2025)
Welcome to Study & Scrutiny, Issue 7.1. For the 10th anniversary issue of Study and Scrutiny, we present a robust issue combined with recent scholarship and selected articles representing ten years of this journal’s contributions to the field of Research on Young Adult Literature.